2009
DOI: 10.1523/jneurosci.0753-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Recall of Spontaneous Activity Patterns in Cortical Networks

Abstract: Irregular ongoing activity in cortical networks is often modeled as arising from recurrent connectivity. Yet it remains unclear to what extent its presence corrupts sensory signal transmission and network computational capabilities. In a recurrent cortical-like network, we have determined the activity patterns that are better transmitted and self-sustained by the network. We show that reproducible spiking and subthreshold dynamics can be triggered if the statistics of the imposed external drive are consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 47 publications
(53 reference statements)
1
31
0
Order By: Relevance
“…It should be noted that such networks are not able to maintain self-sustained activity by themselves. Several studies previously reported that these ongoing and reverberating regimes could be observed in networks with conductance-based synapses (Vogels and Abbott 2005;Kumar et al 2008;El Boustani and Destexhe 2009;Marre et al 2009), but they were all achieved in networks without any propagation delays. We empirically noticed that the linear propagation time taken into account here (see Section 2) increases the average synaptic delay and therefore the neuron density that would have been necessary to observe such a spontaneous regime.…”
Section: Response Under Unstructured Noisementioning
confidence: 96%
See 1 more Smart Citation
“…It should be noted that such networks are not able to maintain self-sustained activity by themselves. Several studies previously reported that these ongoing and reverberating regimes could be observed in networks with conductance-based synapses (Vogels and Abbott 2005;Kumar et al 2008;El Boustani and Destexhe 2009;Marre et al 2009), but they were all achieved in networks without any propagation delays. We empirically noticed that the linear propagation time taken into account here (see Section 2) increases the average synaptic delay and therefore the neuron density that would have been necessary to observe such a spontaneous regime.…”
Section: Response Under Unstructured Noisementioning
confidence: 96%
“…In this paper, we chose to study a more realistic two-dimensional network of integrate-and-fire neurons, which is more relevant biologically since it includes propagation delays (Bringuier et al 1999;Benucci et al 2007) and conductance-based synapses (Vogels and Abbott 2005;Cessac and Viéville 2008;Kumar et al 2008;Marre et al 2009). We provide a detailed numerical study of its spatio-temporal correlations for Gaussian connectivity profiles, previously introduced in the context of information processing (Mehring et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, synaptic weights directly change the network dynamics and vice versa (Lubenov and Siapas, 2008). For appropriate parameters, balanced networks of integrate-and-fire neurons can display asynchronous irregular (AI) states (Brunel, 2000;Vogels and Abbott, 2005;Kumar et al, 2008;El Boustani and Destexhe, 2009;Marre et al, 2009) that produce spike discharge patterns similar to those reported in awake animals (Steriade, 2001;El Boustani et al, 2007). Recurrent neuronal networks have been studied with weight-independent STDP rules (Izhikevich et al, 2004;Morrison et al, 2007;Kang et al, 2008;Lubenov and Siapas, 2008;Gilson et al, 2010).…”
Section: Stable Learning In a Recurrent Network With Stochastic-like mentioning
confidence: 99%
“…Although there have been theoretical studies for over a decade that attempted to characterize the spontaneous activity (Amit & Brunel, 1997;Destexhe & Contreras, 2006), the relationship between the spontaneous and evoked activities as well as its response against external input has not yet been fully elucidated (Marre, Yger, Davison, & Fregnac, 2009). To analyze this relationship, we have focused on memories of the input/output (I/O) map, one of the principle functions of the neural system, and proposed a novel viewpoint of memory (Kurikawa & Kaneko, 2011), which we have termed ''memories as bifurcations''.…”
Section: Introductionmentioning
confidence: 99%